(untitled) (European Journal of Formal Sciences and Engineering, 2025)
During this century, the Leskoviku-Korca-Oher fault zone seismicity is dominated by 7 moderate earthquakes with magnitude ML ranging 4.5 – 5.3. The database of this study composed of 2858 seismic events with ML >0.5 is characterized by tectonic earthquakes with b-value 0.76. Most of the earthquakes have magnitude ranging between 1.8 and 3.3. The cumulative number of earthquakes during two decades trends to increase. Furthermore, on the Leskoviku-Korca-Oher territory there are approximately 1392 earthquakes with magnitude ML ≥2.0, about 355 earthquakes ML ≥3.0 with average depth 11km, about 30 earthquakes ML ≥4.0 also 9 earthquakes ML ≥4.5 and 4 earthquakes ML ≥5.0. Statistics from 2001 to 2023 show that every year inside the Leskoviku-Korca-Oher territory occurs one earthquake with ML >4.0 and every 5 years occurs an earthquake with a magnitude of 5.1 to 5.3 Richter. A series of earthquakes of maximal magnitude (ML =5.3) started on June 01, 2019, at 04:26 (UTC), close to Floq village about 17 km south-west of Korça town expresses the increased seismic activity of the Leskovik-Korca-Oher seismogenic zone. We present results from statistics and analysis of focal mechanism of seismic events. The region affected enormous small earthquakes and by some moderate earthquakes during this century together with the strongest earthquake of the May 1960 ML= 6.2, forms a roughly N−S trending active seismotectonic zone in southeastern Albania which presents a threat to nearby urban areas from Albania, Greece and the North-Macedonia.